EMOTIONAL VERBS IN ANGKOLA-MANDAILING LANGUAGE: A NATURAL SEMANTIC METALANGUAGE APPROACH - Ilham Sahdi Lubis; Mulyadi Mulyadi (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2020)
This study examines emotional verbs in Angkola-Mandailing language. This study aims to look at the semantic structure of the emotional verbs in Angkola-Mandailing language to obtain an appropriate picture in interpreting the words of angry emotions after being paraphrased and expressed according to the respective theory used. This research uses the theory of natural semantic metalanguage pioneered by Wierzbicka. This research is expected to be a reference for Angkola-Mandailing community to clarify the real meanings behind the verbs of anger by means of descriptive qualitative method. The research results show that there are 15 elements of emotional verb referring to 'anger'. The words are paraphrased and applied to determine the final meanings of the words so that there is no ambiguity in the meaning. The basic emotions of anger in Angkola-Mandailing are limited by ‘X doing something bad to Y but Y does not necessarily want to be treated so.’